Enseñar, un viaje en cómic - Ayers, William, 1944-; Alexander-Tanner, Ryan (Ediciones Morata, 2013)
"This graphic novel brings to life William Ayers's bestselling memoir To teach : the journey of a teacher, third edition. From Ayers's early days teaching kindergarten, readers follow this renowned educational theorist on his 'voyage of discovery and surprise.'